Permainan “HAKASI” sebagai Inovasi Pembelajaran Pendidikan Pancasila untuk Meningkatkan Motivasi Belajar Siswa di Sekolah Dasar - Febriyantika Wulandari; Muhaini Muhaini; Vivi Alfirra (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study was motivated by the low level of learning motivation among fifth-grade students in Pancasila Education classes at Sungai Lung Public Elementary School. The study aimed to describe the implementation of the educational game “HAKASI” (Pancasila Treasure Hunt) and to examine its effectiveness in enhancing students’ learning motivation through Classroom Action Research (CAR) conducted in two cycles. The research involved 17 fifth-grade students, while the instruments consisted of observation sheets and a learning motivation questionnaire developed based on Hamzah B. Uno’s indicators. The findings revealed that the implementation of the HAKASI game through collaborative activities and Pancasila-based problem-solving tasks significantly improved students’ enthusiasm, cooperation, critical thinking, and active participation in learning. The average learning motivation score increased from 39 in Cycle I (high category) to 45.88 in Cycle II (very high category). All students also achieved scores above the minimum passing grade (KKM) of 75 in Pancasila Education. These findings indicate that the HAKASI game serves as an effective and innovative game-based learning strategy to strengthen students’ motivation and facilitate a contextual understanding of Pancasila values in elementary education.